2016
DOI: 10.1016/j.jctube.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the antimycobacterial activity of novel lipophilic agents by the modified broth based method

Abstract: Most of the introduced susceptibility methods of Mycobacterium tuberculosis have some disadvantages for screening. Therefore, the selection of susceptibility assay for evaluating candidate agents must be determined case by case. In this study, we evaluated the validity of a modified broth dilution-based assay in comparison to the gold standard proportional method for microbial sensitivity test of new lipophilic compounds candidate as antitubercular agents. The in-vitro susceptibilities of 114 M. tuberculosis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The phytochemical analysis of the chloroform fraction revealed the presence of alkaloid, tannin, flavonoid, phenol, saponin and coumarin. The presence of these families of compounds in fraction confirms the results of previous studies on the extracts of I. gabonensis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. These phytochemicals confirm the pharmacological properties reported previously such as anti-ulcer and anti-diarrhoea [23], antioxidant [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], anti-inflammatory [6], anti-cancer [25] and anti-microbial activities [11][12][13][14][15]…”
Section: Phytochemical Analysissupporting
confidence: 85%
See 3 more Smart Citations
“…The phytochemical analysis of the chloroform fraction revealed the presence of alkaloid, tannin, flavonoid, phenol, saponin and coumarin. The presence of these families of compounds in fraction confirms the results of previous studies on the extracts of I. gabonensis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. These phytochemicals confirm the pharmacological properties reported previously such as anti-ulcer and anti-diarrhoea [23], antioxidant [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], anti-inflammatory [6], anti-cancer [25] and anti-microbial activities [11][12][13][14][15]…”
Section: Phytochemical Analysissupporting
confidence: 85%
“…The result obtained reveals highest antifungal activity value against C. albicans at 2.5 mg/mL (5 mm) and lowest activity value for C. albicans at 25 mg/mL (14 mm). The MIC values obtained in this study are compared favourably with those reported in the literature for some of the test organisms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Figs (3 and 4) show the MIC charts for both bacteria and fungi against the chloroform fraction.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 72%
See 2 more Smart Citations